Keeping the whole child healthy and safe : reflections on best practices in learning, teaching, and leadership - Scherer, Marge, 1945- (ASCD, 2010)
This e-book, a collection of articles from Educational Leadership and other ASCD publications, explores what it means to foster health and safety for students. Knowing that what we teach kids today will shape their future well-being, the authors look at the issues from many angles, addressing both physical and mental health and safety. This fourth in a four-book series of e-books on educating the whole child recognizes that although health and safety are not just curriculum topics, they definitely should be formal parts of learning.